Synthesis of New Piperazino Oxadiazoles as Antiparkinsonian Agents - Agarwal, Rishu; Sahay, Alok; Dwivedi, Sudhanshu (Asian Journal of Chemistry, 2010)
Some novel piperazino oxadiazoles have been synthesised and their biological activity have been evaluated. These compounds exhibited moderate to good antiparkinsonian activity.